Analysis of Impacts and Challenges of Online Learning During the Covid-19 Pandemic: A Case Study at SMA Negeri 2 Rantau Selatan - Sitompul, Nurlaila; Siregar, Zunaidy Abdullah (Bioscientist : Jurnal Ilmiah Biologi, 2024)
The COVID-19 pandemic outbreak in 2019 significantly impacted various aspects of societal life, particularly in education. The shift to online learning, necessitated by the pandemic, posed numerous challenges for teachers and students at SMA Negeri 2 Rantau Selatan. This study aims to comprehensively understand these difficulties faced by 11th-grade teachers during online instruction. Employing a qualitative descriptive approach, the findings reveal several challenges: difficulties in delivering the curriculum, evaluating students' understanding, and creating engaging online learning environments. Quantitatively, 75% of teachers reported significant challenges in curriculum delivery, 60% found it difficult to assess students' comprehension, and 70% struggled with maintaining student engagement. These findings suggest a need for more active and creative teaching methods, supported by adequate facilities from the government. The implications of these findings highlight the necessity for improved educational practices and policy recommendations to better support online learning.